Modeling of near - Wellbore permeability reduction due to depletion of a naturally fractured reservoir - Alvarez, L. L. (2020)
Naturally fractured reservoirs are complex systems to characterize and predict. It is important to establish some basic criteria to identify when fractures are an important element in reservoir performance and also recognize the nature and characteristics of a naturally fractured reservoir. These fractures are present in almost all hydrocarbon reservoirs and their importance is can change the permeability and flow path of the porous media. This paper presents_the case study of a 2D well producer where the surrounding permeability is reduced due to the depletion. This affects the geomechanical behavior of the fractures aperture. The model was simulated in a numerical code (CODE_BRIGHT) using the strong discontinuity approach to embed discontinuities in a finite element mesh and provides a numerical fluid flow analysis in a deformable reservoir. The permeability has been determined as a function of the fracture closure obtained by the mechanical model. Since the rock permeability was considered almost absent, the fluid flow takes place through the natural fractures network. The depletion of the well can close the fractures and drastically reduce the overall permeability of the formation.